1990
DOI: 10.1128/jvi.64.7.3407-3416.1990
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus nuclear antigen 2 transactivates latent membrane protein LMP1

Abstract: Several lines of evidence are compatible with the hypothesis that Epstein-Barr virus (EBV) nuclear antigen 2 (EBNA-2) or leader protein (EBNA-LP) affects expression of the EBV latent infection membrane protein LMP1. We now demonstrate the following. (i) Acute transfection and expression of EBNA-2 under control of simian virus 40 or Moloney murine leukemia virus promoters resulted in increased LMP1 expression in P3HR-1-infected Burkitt's lymphoma cells and the P3HR-1 or Daudi cell line. (ii) Transfection and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
120
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(125 citation statements)
references
References 46 publications
(65 reference statements)
2
120
1
Order By: Relevance
“…4A). This little or no effect in the transiently EBNA-2-expressing cells in this study is well consistent with the experimental result of EBNA-2 on the activity of SV40 promoter in pSV2CAT mentioned by Wang et al (49).…”
Section: Ebna-2 Expression In Bjab and Dg75 Cellssupporting
confidence: 94%
See 1 more Smart Citation
“…4A). This little or no effect in the transiently EBNA-2-expressing cells in this study is well consistent with the experimental result of EBNA-2 on the activity of SV40 promoter in pSV2CAT mentioned by Wang et al (49).…”
Section: Ebna-2 Expression In Bjab and Dg75 Cellssupporting
confidence: 94%
“…It has been recently reported that EBNA-2 exerted a simulatory effect on the level of c-fgr RNA (19) and an interference with the interferon-induced anti-proliferative response (2). It has been also reported that EBNA-2 transactivated the expression of LMP1 and the terminal protein (LMP2) which are encoded by the EBV genome (1,14,49,50). Thus, EBNA-2 is considered to hold multiple effects on the expression of a variety of cellular and viral genes.…”
Section: Cell Surface Antigens On Ebna-2-expressing Cellsmentioning
confidence: 99%
“…Some simian EB viruses can immortalize B cells in vitro (Rabin et af., 1977), although this remains to be established for cyno-EBV. However, EBNA2 has multiple other functions, including regulation of LMPl expression and EBNA transcription (Wang et at,, 1990). No LMPl reactivity could be demonstrated in the monkey lymphoma cells with 2 monospecific reagents, which is in line with the low homology of the LMP-coding sequence between EBV and cyno-EBV (Feichtinger et al,199%).…”
Section: Discussionmentioning
confidence: 90%
“…In Southern blotting, a homologous DNA region was also detected by a probe covering the right part of the BYRF1-exon. EBNA2 has been shown to be necessary for initiation of EBV-induced immortalization (Cohen et al, 1989), to induce the viral LMP1, the NFkB transcription factor and several cellular proteins, in particular the CD 21-CD 23 complex, which may serve as an autocrine growth factor of EBV-infected B cells (Wang et aL, 1990(Wang et aL, , 1991. It is of interest that a CD23 cross-reacting protein was also found in most monkey lymphomas (Li et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that a CD23 cross-reacting protein was also found in most monkey lymphomas (Li et al, 1993). EBNA2 is also involved in the regulation of several promoters for other latent viral proteins, the BCRZpromoter, and the promoters controlling expression of LMP1, LMP2a and LMP2b (Fahraeus et al, 1990;Wang et al, 1990). One may assume that CYNA2 has similar vital functions.…”
Section: Discussionmentioning
confidence: 99%